Endothelial alkalinisation inhibits gap junction communication and endothelium‐derived hyperpolarisations in mouse mesenteric arteries. (11th February 2013) - Boedtkjer, Ebbe; Kim, Sukhan; Aalkjaer, Christian
Key points Gap junctions are important for coordination and transfer of signals between cells. Signals initiated in the vascular endothelium can spread through myoendothelial gap junctions and cause relaxation of coupled vascular smooth muscle cells. The cellular level of acidity is important for control of vascular function. The mechanisms linking disturbed acid–base balance to changes in vascular tone have not been understood in detail. We show that intracellular alkalinisation of endothelial cells in resistance arteries inhibits myoendothelial coupling and endothelium‐dependent vasorelaxation. Although hyperpolarisations are generated in the endothelial cells under alkaline conditions, they are not transferred to the smooth muscle cells. Similarly, dye transfer between endothelial cells is inhibited during intracellular alkalinisation. These results support the suggestion that intracellular pH is important for control of gap junction conductivity and intercellular communication. We describe a potential new molecular mechanism for development of vascular dysfunction in pathologies (e.g. diabetes, hypertension) involving altered myoendothelial signalling. Abstract Gap junctions mediate intercellular signalling in arteries and contribute to endothelium‐dependent vasorelaxation, conducted vascular responses and vasomotion. Considering its putative role in vascular dysfunction, mechanistic insights regarding the control of gap junction conductivity are required. Here, we investigated the consequences of endothelial alkalinisation for gap junction communication and endothelium‐dependent vasorelaxation in resistance arteries. We studied mesenteric arteries from NMRI mice by myography, confocal fluorescence microscopy and electrophysiological techniques. Removing CO2/HCO3−, reducing extracellular [Cl−] or adding 4, 4′‐diisothiocyanatostilbene‐2, 2′‐disulphonic acid inhibited or reversed Cl−/HCO3− exchange, alkalinised the endothelium by 0.2–0.3 pH units and inhibited acetylcholine‐induced vasorelaxation. NO‐synthase‐dependent vasorelaxation was unaffected by endothelial alkalinisation whereas vasorelaxation dependent on small‐ and intermediate‐conductance Ca2+‐activated K+ channels was attenuated by ∼75%. The difference in vasorelaxation between arteries with normal and elevated endothelial intracellular pH (pHi) was abolished by the gap junction inhibitors 18β‐glycyrrhetinic acid and carbenoxolone while other putative modulators of endothelium‐derived hyperpolarisations – Ba2+, ouabain, iberiotoxin, 8Br‐cAMP and polyethylene glycol catalase – had no effect. In the absence of CO2/HCO3−, addition of the Na+/H+‐exchange inhibitor cariporide normalised endothelial pHi and restored vasorelaxation to acetylcholine. Endothelial hyperpolarisations and Ca2+ responses to acetylcholine were unaffected by omission of CO2/HCO3−. By contrast, dye transfer between endothelial cells and endothelium‐derived hyperpolarisations of vascular smooth muscle cells stimulated by acetylcholine or the proteinase‐activated receptor 2 agonist SLIGRL‐amide were inhibited in the absence of CO2/HCO3−. We conclude that intracellular alkalinisation of endothelial cells attenuates endothelium‐derived hyperpolarisations in resistance arteries due to inhibition of gap junction communication. These findings highlight the role of pHi in modulating vascular function.